Islamic Education Curriculum Reform: Global Insights from a Bibliometric Study - A. Ansorullah; Benny Prasetiya; Febry Suprapto; Khoiriyah (Immortalis Journal of Interdisciplinary Studies, 2026)
Islamic education curriculum reform has become a strategic global issue in response to the need for an educational system that is adaptive to globalisation, digitalisation, and the plurality of values. This study aims to map global trends in Islamic education curriculum reform through a bibliometric approach and scientific network visualisation based on Scopus and Web of Science data (2019–2024), using the PRISMA 2020 framework. The results show a significant increase in publications (an average of 8.84% per year), dominated by Southeast Asia, particularly Indonesia and Malaysia. Thematic analysis reveals four main clusters: Islamic education curriculum education (a foundational theme), religion–Islam–culture (a motor theme), human–teaching (a humanistic pedagogical foundation), and humans–questionnaire–Saudi Arabia (a cross-cultural empirical theme). Theoretically, these findings confirm a paradigm shift towards Integrative Curriculum Theory, which integrates spiritual values (maqaṣid al-shari‘ah), 21st-century competencies, and digital innovation. This research also reinforces the relevance of Critical Islamic Pedagogy and Digital Islamic Pedagogy in developing value-based, technology-enhanced, and human-centred curricula. These findings provide a scientific basis for adaptive, evidence-based Islamic education policy and contribute to SDG 4 on Quality Education, as well as to the development of globally competitive human resources with strong character.